Vaccination: Considerations to acceptance and refusal - Sinaga, Doni Marisi (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Abstract is not required for this Editorial. Below are the summary and keywords the journal provides for insight to our reader. Vaccination is one efficient and crucial tool for preventing and controlling disease. This short review questions what factors lead to acceptance and refusal of vaccines in society. This editorial has 4 sub-bab: 1) CULTURAL FACTORS INHIBITING IMMUNIZATION PROGRAM 2) POLITICAL PROPOGANDA INHIBITING IMMUNIZATION PROGRAM 3) IMMUNIZATION IN PROGRESS, and 4) POTENTIAL CHALLENGES. Received: 15 January 2018; Reviewed: 23 January 2018; Received in revised form: 22 February 2018; Accepted: 28 February 2018.